Modification in energy and productivity of high-temperature variable pressure humidification–compression - Abedi, Marzieh; Ghalavand, Younes (Water science & technology. Water supply, 2021)
One of the important approaches in thermal desalination processes is consumed energy reduction. To achieve this aim, three arrangements of humidification–compression (HC) processes are designed. Two single-stage processes and one double-stage HC process are designed and their performances are compared based on desalinated water production, gained output ratio (GOR) and power consumption. An attempt is made to reduce the power consumption and improve the system performance. All three processes are simulated to examine the effect of operation parameters on HC performance. To validate these simulations, the theoretical results are compared with an experimental rig with a humidifier column of 1.5 m height. The results indicate that the simulation values conform to the experimental data. The effect of minimum approach temperature (ΔTmin) on system performance is investigated for three processes subject to constant operating conditions (feed temperature, water mass flow, air mass flow, and pressure ratio). For this purpose, four values of ΔTmin are considered (7.5, 10, 12.5 and 15 °C) for heat exchanger operations. The results indicate that an increase in ΔTmin in all three cases increases desalinated water volume and GOR. Also, the double-stage HC system has higher water production rate (66.08 kg/h) and higher GOR (17.19) compared with its counterparts.